2015
DOI: 10.1007/s13246-014-0325-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement uncertainty analysis of low-dose-rate prostate seed brachytherapy: post-implant dosimetry

Abstract: The minimal dose covering 90 % of the prostate volume--D 90--is arguably the most important dosimetric parameter in low-dose-rate prostate seed brachytherapy. In this study an analysis of the measurement uncertainties in D 90 from low-dose-rate prostate seed brachytherapy was conducted for two common treatment procedures with two different post-implant dosimetry methods. The analysis was undertaken in order to determine the magnitude of D 90 uncertainty, how the magnitude of the uncertainty varied when D 90 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…125 I brachytherapy was a feasible treatment modality for bone metastases in this study, with a success rate of up to 97.6%. According to disease progression, we could implant the 125 I seeds to the same or other lesions after the first treatment cycle without increasing the risk of complications (21). In this study, TPS was used to plan 125 I seed implantation in accordance with the American Brachytherapy Society guidelines (more than 95% of the tumor receives 100% of the prescribed dose) (12).…”
Section: Discussionmentioning
confidence: 99%
“…125 I brachytherapy was a feasible treatment modality for bone metastases in this study, with a success rate of up to 97.6%. According to disease progression, we could implant the 125 I seeds to the same or other lesions after the first treatment cycle without increasing the risk of complications (21). In this study, TPS was used to plan 125 I seed implantation in accordance with the American Brachytherapy Society guidelines (more than 95% of the tumor receives 100% of the prescribed dose) (12).…”
Section: Discussionmentioning
confidence: 99%
“…values (Gregory, Pattison, & Bibbo, 2015) and V100 (volume that is receiving 100% of the prescribed dose) has been reported to be extremely sensitive to prostate contouring errors and uncertainties (Mashouf et al, 2016). Recently magnetic resonance imaging (MRI) has been introduced to the LDR post-implant dosimetry workflow to benefit from its superior soft-tissue contrast (Ash et al, 2000;Davis et al, 2012;Segedin & Petric, 2016).…”
Section: Low Dose Rate Brachytherapymentioning
confidence: 99%
“…Although a D 90 > 130 Gy is considered adequate by the American Brachytherapy Society [8], various studies have shown that a D 90 ≥ 140 Gy is associated with improved biochemical control [9, 10]. Previous studies have found that specific factors such as prostate volume, post-implant prostatic edema, and the number of seeds implanted can influence D 90 [11, 12, 13]. …”
Section: Purposementioning
confidence: 99%